Household mobility in food purchasing during COVID-19 lockdown: Evidence from Torino, Italy. (March 2022) - Braut, Beatrice; Migheli, Matteo; Truant, Elisa
Abstract: During the first wave of COVID-19, lockdown restrictions limited people's movements mainly to food purchasing. Using survey data collected in Torino, Italy, from university students, this study analyses the lockdown's impact on the transportation means used for purchasing food compared to the pre-lockdown period. Food store businesses were not limited by the restrictions and people had to purchase food; however, national and local rules limited citizens' movements, potentially leading to a different choices of transportation means than before the pandemic. The results show that both the lockdown and, perhaps, the fear of contagion, moved the preferences of people from public and shared means to foot and private vehicles. These findings can help in rethinking how transportation is organised in an urban environment, such as that in Torino. Ensuring the safety of public and shared transportation may help sustain mobility during health emergencies. Highlights: Lockdowns due to Covid-19 pandemic have changed our behaviours. Mobility was particularly affected. The paper focusses on this. Data are from university students in Torino, Italy, and their mobility for food purchasing. The pandemic moved preferences from public transportation to feet and private cars. Strengthening public transportation is recommended.